EFEKTIVITAS TABLET FE DAN BISKUIT TEPUNG BIJI SALAK DALAM MENINGKATKAN ASUPAN ZAT BESI, ZINC DAN VITAMIN C PADA REMAJA PUTRI DENGAN ANEMIA - Budiyanti, Novita; Indarto, Dono; Handayani, Selfi (Media Penelitian dan Pengembangan Kesehatan, 2024)
Iron nutritional anemia is a prevalent health issue among adolescent girls. Several factors contribute to anemia in this demographic, including inappropriate growth for age, poor nutritional intake, unhealthy food habits, inadequate or excessive physical activity, irregular menstrual cycles, and lack of nutrition knowledge. To address this, the government has implemented supplementation programs with iron tablets. Additionally, utilizing local foods rich in iron presents a potential complementary strategy.This study aimed to analyze the effect of salak seed flour biscuits (TBS) on the intake of iron (Fe), zinc (Zn), and vitamin C in anemic adolescent girls.This research was designed as a randomized controlled trial (RCT) with a pretest-posttest control group design. The study involved 33 anemic adolescent girls from Indramayu Regency. Data collection methods included interviews using structured questionnaires, 24-hour food recall forms, and anthropometric measurements of body weight and height. Data were analyzed using one-way ANOVA, followed by Bonferroni post hoc tests.The results indicated that the administration of TBS biscuits significantly increased the intake of Fe, Zn, and vitamin C in all groups. Notably, TBS biscuits containing 4.17 mg of Fe per 100 g showed the highest increase in nutrient intake. Over a 60-day period, these biscuits significantly boosted the intake of Fe, Zn, and vitamin C in anemic adolescent girls.The study concluded that TBS biscuits are an effective intervention for increasing the intake of essential nutrients in anemic adolescent girls. The inclusion of such fortified local foods can be a valuable addition to existing anemia prevention programs.